2016
DOI: 10.1093/conphys/cov069
|View full text |Cite
|
Sign up to set email alerts
|

Links between parasitism, energy reserves and fecundity of European anchovy,Engraulis encrasicolus, in the northwestern Mediterranean Sea

Abstract: This study assesses, for the first time, the interrelationships between size, fecundity, energy reserves and parasitism in female European anchovy, in order to analyse the potential implications for the health of the northwestern Mediterranean anchovy stock arising from the current shortage of large individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…In the light of the current small pelagic fish situation in the Gulf of Lions, characterized by small sardine and anchovy in poor condition [33,54], our results indicate that the individual reproductive potential could be strongly affected both in terms of quantity and quality. However, earlier maturation could potentially lead to a higher number of breeders and compensate at the population level for the decrease in individual reproductive capacity, as described in other short-lived species such as Daphnia [92] or insects [93].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the light of the current small pelagic fish situation in the Gulf of Lions, characterized by small sardine and anchovy in poor condition [33,54], our results indicate that the individual reproductive potential could be strongly affected both in terms of quantity and quality. However, earlier maturation could potentially lead to a higher number of breeders and compensate at the population level for the decrease in individual reproductive capacity, as described in other short-lived species such as Daphnia [92] or insects [93].…”
Section: Discussionmentioning
confidence: 93%
“…Three sieves with a mesh size ranging from 600 to 250 µm were used to sort the oocytes by size. Oocyte size distribution followed a bimodal distribution and eggs belonging to the next batch were counted based on their size as defined in [39,54] for anchovy. Counting of oocytes was performed with an image analysis system (Image-Pro Plus 5.1; ).…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly clear for anchovy in some areas, such as the NW Mediterranean, where small sized less fecund individuals presenting lower fecundity (McBride et al, 2015) in a low health status (i.e. lower lipid content and higher intensity of certain parasites, Ferrer-Maza et al, 2016a are dominant in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, condition indices can be computed easily from collected length and weight data, available in numerous areas and at large temporal scale. It has already been demonstrated that environmental factors, such as temperature, food availability (Brosset et al, 2015b) or parasitism (Ferrer-Maza et al, 2016b) influence fish condition through direct and/or indirect effects. For example, a decrease in body condition due to a lack of food or an increase of metabolic costs under higher temperature has already been advocated in several studies (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Simple measures of condition factor and energy reserves are informative physiological biomarkers of population health ( Claireaux et al ., 2004 ; Jeffrey et al ., 2015 ) that, in this Theme Section, are applied as biomarkers for effects of parasitism in a small pelagic species, the European anchovy ( Engraulis encrasicolus ), in the northwest Mediterranean ( Ferrer-Maza et al ., 2016 ). Some studies have measured physiological indicators of whole-animal performance, such as swimming ability, or hypoxia and thermal tolerance, including measurements on fishes in mesocosms or caged at specific sites ( Claireaux et al ., 2004 ; McKenzie et al ., 2007 ; Roze et al ., 2013 ).…”
Section: Applications For Physiological Biomarkersmentioning
confidence: 99%